2014
DOI: 10.1177/0960327114557901
|View full text |Cite
|
Sign up to set email alerts
|

Edible mushroom-related poisoning

Abstract: Background: The American Association of Poison Control Center (AAPCC) shows that in 2012 there were 0.3% of human exposures involving mushrooms. Only 17% of 6600 cases were then identified by the species. The present retrospective study was designed to identify the epidemiology of mushroom poisoning in adults admitted to Krakow’s Department of Clinical Toxicology (DCT) from 2002 to 2009. Materials and Methods: Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 16 publications
4
22
0
Order By: Relevance
“…Unfortunately, wild edible mushrooms grow seasonally only; therefore, an alternative is to supplement Se using cultivated mushrooms, especially those which are economically important such as species of Pleurotus, Pholiota or Agaricus genera [19][20][21]. It should be highlighted that in many countries and regions, the consumption of mushrooms constitutes an important and integral part of the human diet [22].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, wild edible mushrooms grow seasonally only; therefore, an alternative is to supplement Se using cultivated mushrooms, especially those which are economically important such as species of Pleurotus, Pholiota or Agaricus genera [19][20][21]. It should be highlighted that in many countries and regions, the consumption of mushrooms constitutes an important and integral part of the human diet [22].…”
Section: Introductionmentioning
confidence: 99%
“…During the same period, 15 poisoning cases with mushrooms considered edible were noted. A summary on mushroom poisoning in Poland indicated that species such as Macrolepiota procera or Imleria badia are a more common cause of gastrointestinal effects than T. equestre [ 14 ]. If one considers the estimated number of Poles consuming T. equestre , the frequency of adverse effects remains very low and there are no cases involving previously reported rhabdomyolysis.…”
Section: Resultsmentioning
confidence: 99%
“…All subjects were collecting T. equestre mushrooms on their own and agreed to undertake additional biochemical tests following their next consumption. According to Polish law regulation established and enforced by the Ministry of Health, T. equestre is considered an edible species and collection from the wild is allowed with no restrictions [ 14 ]. Study protocol was approved by the Bioethical Committee at Poznan University of Medical Sciences (Approval No.…”
Section: Methodsmentioning
confidence: 99%
“…This is due to the large number of species with toxic effects, the difficulties in species identification by both patients and hospital personnel, and the ingestion of mushrooms in meals containing several mushroom species simultaneously. In addition, toxicity may be caused by not only the original biological composition of the fruiting body, but by more conventional types of food poisoning, such as incorrect preservation or processing of mushrooms after harvesting [ 4 ].…”
Section: Introductionmentioning
confidence: 99%